Tubulin C-terminal Post-translational Modifications Do Not Occur in Wood Forming Tissue of Populus - Hu, Hao; Gu, Xi; Xue, Liang-Jiao; Swamy, Prashant S.; Harding, Scott A.; Tsai, Chung-Jui (Frontiers in Plant Science, 2016)
Cortical microtubules (MTs) are evolutionarily conserved cytoskeletal components with specialized roles in plants, including regulation of cell wall biogenesis. MT functions and dynamics are dictated by the composition of their monomeric subunits, α- (TUA) and β-tubulins (TUB), which in animals and protists are subject to both transcriptional regulation and post-translational modifications (PTM). While spatiotemporal regulation of tubulin gene expression has been reported in plants, whether and to what extent tubulin PTMs occur in these species remain poorly understood. We chose the woody perennial Populus for investigation of tubulin PTMs in this study, with a particular focus on developing xylem where high tubulin transcript levels support MT-dependent secondary cell wall deposition. Mass spectrometry and immunodetection concurred that detyrosination, nontyrosination and glutamylation were essentially absent in tubulins isolated from wood-forming tissues of Populus deltoides and P. tremula  alba. Label-free quantification of tubulin isotypes and RNA-Seq estimation of tubulin transcript abundance were largely consistent with transcriptional regulation. However, two TUB isoypes were detected at noticeably lower levels than expected based on RNA-Seq transcript abundance in both Populus species. These findings led us to conclude that MT composition during wood formation depends exclusively on transcriptional and, to a lesser extent, translational regulation of tubulin isotypes.